Nous le passage : Watou 2005 Poëziezomer - Mandelinck, Gwy; Watou (Watou : vzw Poëziezomers-Kunstzomers Watou, 2005)
Atelier van Lieshout ; 't Jolle, Sven ; Beuys, Joseph ; Bismuth, Pierre ; Bratkov, Sergey ; Buggenhout, Peter ; Congost, Carles ; Coplans, John ; Cragg, Tony (Anthony) ; De Bruyckere, Berlinde ; Deleu, Jozef ; Durant, Sam ; Eckart, Christian ; Elmgreen & Dragset ; Fabre, Jan ; Gilbert & George ; Goldin, Nan ; Kruger, Barbara ; Kuri, Gabriel ; Lafont, Suzanne ; Manders, Mark ; Maté, Mateo ; Messager, Annette ; Nauman, Bruce ; Op de Beeck, Hans ; Robinson, Peter ; Roosen, Maria ; Sanguineti, Pietro ; Waddington, Laura ; Wambacq, Freek ; Zaugg, Rémy
Publicatie n.a.v. de tentoonstelling 'Nous le passage: Watou Poëziezomer 2005' in Watou, 02.07.2005-11.09.2005
boek